PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGAION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 11 DOMPAS KECAMATAN BUKIT BATU - Marzuki, Heri; Lazim N, Lazim N; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The problem of this research is the weakness of students result learning in natural science subject at IV class students of SD Negeri 11 Dompas Bukit Batu Subdistrict which is consist of 20 students. The KKM in this school is 66. From the total only 8 students ( 40,00 %) reach the KKM and 12 students (60,00%) under the KKM. Based on the problem, the reseacher doing the research by using implementation cooperative learning model group investigation (GI). In cycle I, the percentage of teacher activity in the first meeting is adquate 54,00 %, in the second meeting teacher activity significantly increase up to 70,00 % with good category. In cycle II, the first meeting was in very good category 83,00% and the second meeting indecated very good category 100 %. Meanwhile, the activity of students also improved. In cycle I, at the first meeting indicated 41,66 % in adquate category and in cycle II has increased up to 66,66 % with good category. In cycle II, the first meeting, the activity of students has been increasing up to 83,33 % with very good category,and the second meeting increase up to 100% with very good category. An average score of students result learning before implementation is 63,55 %, it increased up to 74,50 % in cycle I, and 79,50 % in cycle II. In classical completeness, cycle I and cycle II were achieved. in conclusion the implementation cooperative model investigation group (GI) can improve students result learning at IV class students of SD Negeri 11 Dompas Bukit Batu Subdistrict in natural science subject.Keyword : Cooperative model group investigation (GI) type, result learning in natural science subject.